2022
DOI: 10.3171/2021.6.jns211201
|View full text |Cite
|
Sign up to set email alerts
|

Multiple predictors of in-stent restenosis after stent implantation in symptomatic intracranial atherosclerotic stenosis

Abstract: OBJECTIVE This study aimed to identify predictors of intracranial in-stent restenosis (ISR) after stent placement in symptomatic intracranial atherosclerotic stenosis (ICAS). METHODS The authors retrospectively collected data from consecutive patients who suffered from symptomatic ICAS and underwent successful stent placement in Beijing Tiantan hospital. Eligible patients were classified into “ISR,” “indeterminate ISR,” or “no-ISR” groups by follow-up digital subtraction angiography or CT angiography. A mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
12
1
Order By: Relevance
“…On the other hand, the rate of remedial stent implantation in this study was lower than that in our previous studies 3 4. As we know, elastic recoil after balloon dilation (DCB or CB) is more obvious than after stent, so the residual stenosis might be higher after only balloon dilation, which is also a significant marker of long-term restenosis 5. Therefore, remedial stent implantation might be a reasonable choice for those with obvious residual stenosis.…”
contrasting
confidence: 56%
“…On the other hand, the rate of remedial stent implantation in this study was lower than that in our previous studies 3 4. As we know, elastic recoil after balloon dilation (DCB or CB) is more obvious than after stent, so the residual stenosis might be higher after only balloon dilation, which is also a significant marker of long-term restenosis 5. Therefore, remedial stent implantation might be a reasonable choice for those with obvious residual stenosis.…”
contrasting
confidence: 56%
“…Previous studies had made some efforts to explore the risk factors for ISR and sISR, however, no definite consensus was reached. Some reported that increased residual stenosis independently predicted recurrent stroke ( 10 , 38 , 39 ). Conversely, a meta-analysis showed a close relationship between lower residual stenosis and higher incidence of sISR, which might be true because lower residual stenosis implied greater arterial and endothelial injury that promoted inflammation and plaque progression thus simulating ISR ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In-stent restenosis (ISR) after PTAS was associated with almost 80% of postprocedural ischemic stroke events ( 10 ). The 1-, 2-, and 3-year rate for symptomatic ISR (sISR) in the SAMMPRIS trial (Stenting and Aggressive Medical Management for the Prevention of Recurrent Stroke in Intracranial Stenosis) were 9.6, 11.3, and 14.0%, respectively, ( 11 ) and 10.9% in the US Wingspan Registry trial ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that elevated oxLDL has been associated with increased plaque instability in patients undergoing carotid endarterectomy 22 and high levels of hs‐CRP have also been proved to be significantly associated with stroke recurrence in patients with symptomatic intracranial atherosclerotic stenosis after intracranial stent implantation. 23 In addition, endothelial dysfunction is the first step in the development of an atherosclerotic plaque and local inflammation. 24 OxLDL and hs‐CRP can also affect the clinical outcome of stroke by damaging endothelial cells.…”
Section: Discussionmentioning
confidence: 99%